2016
DOI: 10.1039/c6tc02142e
|View full text |Cite
|
Sign up to set email alerts
|

Improved charge carrier transport in ultrathin poly(3-hexylthiophene) films via solution aggregation

Abstract: Field-effect transistors based on poly(3-hexylthiophene) (P3HT) ultrathin films exhibit maximum charge carrier mobilities of up to 0.1 cm2 V−1 s−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 36 publications
2
48
0
Order By: Relevance
“…7 . In recent studies, DSC crystallinity calculation has largely been used to validate X-ray diffraction (XRD) results [ 40 , 41 ]. The authors' previous study [25] showed that PVA nanofiber has a low degree of crystallinity, and this agrees with XRD results.…”
Section: Resultsmentioning
confidence: 99%
“…7 . In recent studies, DSC crystallinity calculation has largely been used to validate X-ray diffraction (XRD) results [ 40 , 41 ]. The authors' previous study [25] showed that PVA nanofiber has a low degree of crystallinity, and this agrees with XRD results.…”
Section: Resultsmentioning
confidence: 99%
“…39,40 Films obtained from preaggregated solutions exhibit a fibrous microstructure, even in the case of ultrathin films spin-coated at very high rotation speeds. 41 This polymer preaggregation enables high mobilities in ultrathin films. Therefore, a thin fibrous P3HT film (Fig.…”
Section: Bilayer Film Structurementioning
confidence: 99%
“…Semiconducting conjugated polymers (CPs) offer a viable alternative due to their facile solution processability, flexibility, and tailor‐made synthetic versatility . However, molecular self‐assembly driven and morphology‐dependent device performances require critical attention to the judicious selection of suitable thin‐film fabrication techniques . Charge transport in CPs essentially involves intramolecular (within conjugated backbone), intermolecular (through π‐π stacking of adjacent, stacked, conjugated backbones), and intermolecular interdomain hopping …”
Section: Introductionmentioning
confidence: 99%